9514 1404 393
Answer:
x = 69 4/9
Step-by-step explanation:
There are a couple of approaches you can take to this. The usual one would be to "clear fractions" by multiplying by 15.
15(3/5x) +15(1/3) = 15(42)
9x +5 = 630
Now, we can subtract 5 and divide by 9.
9x = 625 . . . . subtract 5 from both sides
x = 625/9 = 69 4/9
__
Another way to solve this is to multiply by 5/3 to make the coefficient of x be 1.
(5/3)(3/5x) +(5/3)(1/3) = (5/3)(42)
x +5/9 = 70
Now, we can subtract 5/9 from both sides.
x = 69 4/9
__
Working it in the usual "two-step equation" manner, you would subtract 1/3 first, then multiply by 5/3. IMO, this is messier, as you have ...
(5/3)(3/5x) = (5/3)(41 2/3)
x = (5/3)(125/3) = 625/9 = 69 4/9